2016
DOI: 10.1363/48e8716
|View full text |Cite
|
Sign up to set email alerts
|

Women's Knowledge of and Support for Abortion Restrictions in Texas: Findings from a Statewide Representative Survey

Abstract: CONTEXT States have passed numerous laws restricting abortion, and Texas passed some of the most restrictive legislation between 2011 and 2013. Information about women’s awareness of and support for the laws’ provisions could inform future debates regarding abortion legislation. METHODS Between December 2014 and January 2015, some 779 women aged 18–49 participated in an online, statewide representative survey about recent abortion laws in Texas. Poisson regression analysis was used to assess correlates of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
5
23
0
Order By: Relevance
“…There is a substantial gap between the scientific evidence demonstrating the safety of abortion in the US and public opinion about abortion safety [35]. In the present study, approximately half of registered Texas voters believed that the ASC and admitting privileges requirements would make abortion safer and a similar percentage supported these provisions.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…There is a substantial gap between the scientific evidence demonstrating the safety of abortion in the US and public opinion about abortion safety [35]. In the present study, approximately half of registered Texas voters believed that the ASC and admitting privileges requirements would make abortion safer and a similar percentage supported these provisions.…”
Section: Discussionmentioning
confidence: 53%
“…Upon initiating the survey, participants reported their general view on the morality and legality of abortion. Following other studies [5,13], they indicated which statement about abortion came closest to their view: “I believe having an abortion is morally acceptable and should be legal;” “I am personally against abortion for myself, but I don’t believe government should prevent a woman from making that decision for herself;” or “I believe having an abortion is morally wrong and should be illegal.” They also could indicate that they held some other view. We then asked participants about whether they had heard of the ASC requirement that was recently passed in Texas, and, in a separate question, if they had heard of the hospital admitting privileges requirement.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Catholics and evangelical Protestants are the religious groups most likely to be against abortion [19, 20], especially as Evangelicalism gained momentum in the mid-1990s [21]. Even if HAS respondents were unaware of the exact restrictions—as were most women in previous studies [22, 23]—they were nevertheless exposed to extensive media coverage of divisive public debate about abortion [16, 24]. …”
Section: Introductionmentioning
confidence: 99%